The effect of body position and mass centre velocity at toe off on the start performance of elite swimmers and how this differs between gender - Shepherd, I.; Lindley, M. R.; Logan, O.; Mears, A.; Pain, M. T. G.; King, M. (Sports Biomechanics, 2021)
The start in swimming is a crucial phase of a race, where improvements in performance can be made. Twenty-four elite swimmers race pace starts were recorded from five above and below water 50 Hz video cameras. Body position at toe off was calculated from the recordings and consisted of the two-dimensional mass centre position at toe off, and the arm, trunk, front leg and rear leg angles.Horizontal, vertical and resultant velocity of the mass centre at toe off, time to 5 m, 10 m and 15 m were also determined. Whilst time to 5 m (starting performance) differed by 0.17 s between genders, body position at toe off showed no significant differences. The difference in start performance was mainly due to a difference in horizontal velocity at toe off. The relationship between arm angle and start performance warrants further investigation as there was a range of techniques adopted but no clear link to performance. The trunk angle at toe off was correlated to starting performance for both males and females. This study demonstrates that the body position at toe off is no different between genders but is a critical determinant of starting performance for both males and females.